Inverse relationship of oxidative balance score with hyperuricemia among Chinese adults: a population-based cross-sectional study - Hewei Peng; Ying Han; Jingru Huang; Wenxin Qiu; Huajing Chang; Jiangwang Fang; Xian-E Peng (BMC Public Health)
Abstract Background The oxidative balance score (OBS) is a composite metric highlights pro-oxidants and antioxidants balance, representing the overall burden of oxidative stress. This study aims to examine the association between OBS and hyperuricemia in a Chinese population. Methods This study was based on population-based cross-sectional survey data of Fujian province from August 2020 to April 2021. OBS was determined based on 10 food and lifestyle OBS components. The association between OBS and hyperuricemia was investigated using logistic regression analysis. Subgroup analyses identified sensitive populations. Restricted cubic spline (RCS) was performed to examine the potential dose-response relationship. Results A total of 9464 participants were included in the final analysis. An inverse association between OBS and hyperuricemia was observed and remained after adjusting for potential confounders. Each additional unit of OBS was associated with a 4% and 7% reduction in the risk of hyperuricemia in men [OR: 0.96(0.94,0.99)] and women [OR: 0.93(0.90,0.96)], respectively. Participants in the highest quartile had a 22% and 37% lower risk of hypertension compared with the lowest quartile of OBS in men [0.78(0.62,0.97)] and women [OR: 0.63(0.49,0.79)], respectively. There were significant interactions between OBS and gender, hypertension, and dyslipidemia on hyperuricemia (P interaction < 0.05), except for age, education, and diabetes (P interaction > 0.05). A linear dose-response relationship between OBS and the risk of hyperuricemia (P nonlinear = 0.7854) was observed. Conclusions An inverse association as well as dose-response relationship between OBS and hyperuricemia were observed. Increasing antioxidant levels through lifestyle modification may be an effective way to prevent hyperuricemia, especially in women. Large prospective cohort studies and randomized controlled trials are required to verify the effect of OBS on hyperuricemia and elucidate its causal mechanism.